Social Innovation between emancipation and adaptation - Pausch, Markus (Momentum Quarterly, 2018)
Long before its technological and economic conceptualization, innovation was discussed as a social emancipatory process, closely linked to the emergence of modern democracy. The questioning of existing truths and hierarchies is integral part of the term innovation as is the creative creation of alternatives. In this article, the focus is on the different dimensions of social innovation. The diffuse use of the term shall be contrasted with a more categorized understanding of social innovation.
Keywords: Social innovation; emancipation; democracy